Fibroblast Growth Factor 21 (Fgf21) Gene Expression Is Elevated in the Liver of Mice Fed a High-Carbohydrate Liquid Diet and Attenuated by a Lipid Emulsion but Is Not Upregulated in the Liver of Mice Fed a High-Fat Obesogenic Diet. Issue 2 (13th January 2016) - Hao, Lei; Huang, Kuan-Hsun; Ito, Kyoko; Sae-tan, Sudathip; Lambert, Joshua D; Ross, A Catharine
Abstract: Background: Fibroblast growth factor 21 (FGF21) is a regulator of carbohydrate and lipid metabolism; however, the regulation of Fgf21 gene expression by diet remains incompletely understood. Objective: We investigated the effect of a high-carbohydrate (HC) liquid diet, with and without supplementation with a lipid emulsion (LE), and of a high-fat diet (HFD) compared with a low-fat diet (LFD) on the regulation of Fgf21 gene expression in the liver of intact mice. Methods: C57BL/6 male mice were fed standard feed pellets (SFPs), a purified HC liquid diet (adequate in calories and protein), or an HC liquid diet containing an LE at either 4% or 13.5% of energy for 5 wk (Expt. 1) or 1 wk (Expt. 2). In Expt. 3, mice were fed a purified LFD (∼10% fat) or HFD (∼60% fat) or were fed an HFD and given access to a running wheel for voluntary exercise for 16 wk. Results: Fgf21 mRNA in liver and FGF21 protein in plasma were increased by 3.5- to 7-fold in HC mice compared with SFP mice ( P < 0.001), whereas the LE dose-dependently attenuated the induction of Fgf21 expression ( P < 0.05). After 16 wk, hepatic Fgf21 mRNA did not differ between LFD and HFD mice but was dramatically reduced in the HFD+exercise group to <20% of the level in the HFD group ( P < 0.0001). Conclusions: In mice, hepatic Fgf21 expression was upregulated by 1 and 5 wk of feeding a lipogenic HC diet but not by 16 wk of feeding an obesogenic HFD, whereas the addition of fat as an LE to the HC formula significantly reduced Fgf21 gene expression and the plasma FGF21 protein concentration. Our results support a strong and reversible response of hepatic Fgf21 expression to shifts in dietary glucose intake.